Genetic and epigenetic aberrations of ABCB1 synergistically boost the acquisition of taxane resistance in esophageal squamous cancer cells - Sumarpo, Anton; Ito, Kazuma; Saiki, Yuriko; Ishizawa, Kota; Wang, Ruobing; Chen, Na; Sunamura, Makoto; Horii, Akira (Biochemical and biophysical research communications, 2020)
Taxanes are applied as potent chemotherapeutic agents in the treatment of patients with esophageal cancer, but their usefulness is limited, partly because of acquisition of chemoresistance. In our previous study, we established three taxane resistant esophageal cancer cell lines; significant ABCB1 upregulations were found in all three. However, the responsible mechanism(s) still remains an open question. In this study, we explored possible mechanisms that might contribute to upregulation of ABCB1 in taxane resistant cells. ABCB1 gene amplification was found in taxane resistant cell line RTE-1P, but expressional upregulation cannot be explained only by gene amplification, because gene amplification is one order of magnitude or less whereas gene expression is more than two orders of magnitude. In the parental TE-1, ABCB1 expression was upregulated after treatment with 5-azadeoxycytidine and/or trichostatin A; epigenetic mechanisms may be deeply involved. ABCB1 has two promoters; a downstream promoter was found to play the dominant role in taxane resistant esophageal cancer cell lines. Analyses of CpG islands demonstrated that taxane resistant cells showed unmethylated CGI whereas parental cells were dominantly methylated. In conclusion, we propose that both the ABCB1 gene amplification and aberrations in epigenetic mechanisms are responsible for acquisition of taxane resistance in esophageal cancer cells. •ABCB1 is frequently overexpressed in taxane resistant esophageal cancer.•Both genetic and epigenetic aberrations boost acquisition of taxane resistance.•The same mechanism is probably functioning in other chemoresistance-acquisitions.